Error Analysis in Surfaces Reconstruction by Fitting and Interpolation Technique - Tahseen F. Alani; Ammar M. Saleh (Engineering and Technology Journal, 2016)
Error between surfaces is the measurement to give us information how similar or different they are. Moreover, since the data associated with error between two matching surfaces are too huge and further need to be filtered into meaningful information. This research shows the suitable ways to represent error, to achieve data reduction and how detailed. Surfacerepresentations that may then be used as a part of many applications in engineering, clinic, virtual and other CAD applications. The statistical tools analysis of error has been developed to provide effective visual inputs that the designer can interpret of meaningful information. The comparison between two matching surfaces was done by using the differences in elevation techniquesthat called distance error between surfaces. A comparison has been made between the two adopted techniques of surface generation (fitting and interpolation) depending on several standard functions (sine-cosine functions, exponential functions and power functions), where the two techniques (fitting and interpolation) have been applied to analyze the representing error statistically. Then the design results have been implemented in manufacturing three of these surfaces using three axis vertical CNC milling machine tool with ball end mill cutter. By applying the proposed surface models, the similarity factor was found to be ranged between 84.86% for one of the models to 100% for other models that are reconstructed by the adopted fitting and interpolating techniques.